Innovative Approaches to Fake Product Detection: Blockchain and QR Code Synergy - Apeksha Vatte; Giridhar Chinchakar; Akshay Kamble; Rohit Vishwakarma (International Journal of Radio Frequency Innovations, 2024)
For consumers, corporations, and regulatory agencies, the worldwide market's rise of counterfeit goods presents serious issues. Maintaining consumer confidence, guaranteeing product safety, and preserving brand reputation all depend on the ability to identify counterfeit goods. An overview of the different approaches and difficulties associated with spotting counterfeit goods is given in this abstract. First off, the ability to identify sophisticated counterfeit goods is limited by the use of conventional techniques like eye inspection and authenticity labels. Two innovative technologies that have emerged as viable tools for combating counterfeit identification are machine learning algorithms and blockchain technology. Large-scale data analysis using machine learning models can spot trends that point to fake goods, while blockchain technology allows safe product identification and traceability. The ability of counterfeiters to evade detection techniques, the absence of standardised authentication standards, and the complexity of international supply chains are obstacles in the identification of fake products. Furthermore, the sale of counterfeit goods has been made easier by the quick expansion of online marketplaces, making it difficult for customers to tell the difference between real and imitation goods.
Keywords: QR code; blockchain; counterfeit; ethereum; supply chain